Perbedaan Bimbingan Kelompok Teknik Symbolic Model dengan Bimbingan Kelompok Konvensional dalam Peningkatan Efikasi Diri Santriwati - Nahdlatien Habibatil Mubarakah; Rury Muslifar; Wahyu Widyatmoko; Muhaimin Abdillah; Yasintha Sari Pratiwi; Dwi Sona (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to determine the differences between group guidance services with symbolic model techniques and conventional group guidance services in improving the self-efficacy of female students at Ibnu Hasan Islamic Boarding School in Samarinda. This study uses a quantitative approach with a quasi-experimental method with a non-equivalent control group design. The research subjects were 8 female students who were included in the low self-efficacy category based on the self-efficacy scale. They were divided into two groups, namely the experimental group and the control group, each consisting of 4 people. Data collection techniques used a self-efficacy scale, observation, and interviews. The results of the study showed that there was a significant difference in the level of self-efficacy between the experimental group and the control group after being given treatment based on the results of the independent samples t-test, with a sig. (2-tailed) value of 0.001 (p <0.05). The average posttest score of the experimental group was 99.8, higher than the control group of 81.0. Therefore, this study concludes that there is a significant difference between group guidance using the symbolic model and conventional group guidance in improving the self-efficacy of female students. This approach can be an alternative service for guidance and counseling teachers in schools to address low self-efficacy in female students.